The cost-effectiveness of introducing Manual Vacuum Aspiration compared to Dilatation and Curettage for incomplete first trimester abortions at a tertiary hospital in Manzini, Swaziland - Moodley, Saiendhra Vasudevan (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2013.